Assessment of Scatter Radiation Exposure in Diagnostic X-Ray Procedures for Radiation Safety - Majed Moqed Mobereek Alwasari, Lara Saqer Mohammad Alotaibi, Faihan Marzouq Faihan Alotaibi, Fathi Abdullah Ali Aljezani, Abdulmajeed Menwer Jalil Alsulami, Sami Abdulrahman Fardis Alqarni, Ahmed Abdulkhaleq Alzahrani (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Radiation protection in medical X-ray imaging has been a subject of extensive scientific inquiry in recent decades. With diverse equipment and practices, attention has focused not only on patient doses but also on occupational exposure. Shielding requirements are crucial for safeguarding both medical personnel and those in the vicinity from scatter radiation, necessitating detailed investigation. Aim: This study aimed to measure secondary radiation in a conventional radiographic setting, focusing on dose rates and their dependence on radiographic exposure factors such as tube voltage and distance. The research sought to provide insights that could optimize radiation protection for medical personnel and patients, especially in scenarios involving mobile X-ray equipment. Methods: A conventional radiographic system was utilized, equipped with a diagnostic X-ray tube and a three-phase high-voltage generator. Measurements were conducted using an ionization chamber calibrated for ambient dose rate equivalent, positioned at various distances and angles from a cylindrical water phantom. The X-ray field was maintained constant at 40 x 40 cm^2 to simulate a worst-case scenario. Additionally, scatter X-ray energy distribution was evaluated through X-ray spectrometry.